PENGARUH KONSENTRASI PUPUK ORGANIK CAIR DAN PUPUK MAJEMUK TERHADAP HASIL SAWI CAISIM (Brassica chinensis) SISTEM HIDROPONIK RAKIT APUNG: caisim, NPK, pupuk organik cair - Pradipta, Ifenza Hernanda; Ratna Nurhayati, Dewi; Sigit Saputro, Avisema (Innofarm:Jurnal Inovasi Pertanian, 2024)
Research on "The Effect of Liquid Organic Fertilizer Concentration and Compound Fertilizer on the Yield of Caisim Mustard (Brassica chinensis) Floating Raft Hydroponic System" was carried out from 30 December 2023 to 23 January 2024 at Green House CV. Multi Global Agrindo, which is located at Dukuh Klatak, Karangpandan Village, Karangpandan District, Karanganyar Regency, with an altitude of 517 masl. This research aims to determine the interaction of compound NPK and Liquid Organic Fertilizer on the growth and yield of caisim mustard greens in a floating raft hydroponic system. The research method used was factorial with a Completely Randomized Design (CRD) consisting of two factors and including three replications. The research factors have two factors, namely compound NPK treatment and Liquid Organic Fertilizer. The parameters observed include plant height, number of leaves, leaf width, plant stover weight, plant biomass weight, root length, leaf color chart, and organoleptic tests. The data from this research were analyzed using the BNJ test at the 5% level. The results of the research showed that 1) Providing Compound NPK Concentration had a significant effect on Plant Height, Number of Leaves, Leaf Width, Fresh Stove, Fresh Biomass, Plant Biomass, Root Length, Leaf Color Chart, Organoleptic Test 2) Providing liquid Organic Fertilizer treatment had a significant effect on Plant Height, Root Length and Organoleptic Tests 3) The interaction between Compound NPK and Liquid Organic Fertilizer has a significant effect on plant height, root length and leaf color chart. 4) Providing the best treatment in the Liquid Organic Fertilizer concentration treatment of 125 ml/L and NPK 800 ppm which affects the parameters of plant height, root length and leaf color chart.